Teachers and Students Envisioning Mixed Reality Remote Learning: A Qualitative Exploration on Fostering Academic Engagement - Goagoses, Naska; Winschiers-Theophilus, Heike; Auala, Selma; Pope, Nicolas; Rötkönen, Erkki; Itenge, Helvi; Suero Montero, Calkin; Suovuo, Tomi; Sutinen, Erkki (Springer Nature, 2025)
Mixed reality (MR) provides new opportunities and affordances for fostering student engagement in remote learning. The current qualitative case study set out to (1) explore teachers’ perspective of academic engagement in traditional classrooms, (2) explore how teachers’ and students’ envision engaging lessons using MR for remote learning, and (3) extrapolate limitations and affordances for the further development of MR for remote learning. Eight students and four teachers from a primary school in Namibia participated. Each participant wore the HoloLens 2, interacting with others who were live streamed from another room. Group interviews with the teachers revealed core practices and strategies focused on the centrality of students, student-teacher relationships, rewards and evaluations, and the physical environment for creating engagement in traditional classrooms. Teachers and students participated in role-plays centered around fostering emotional, behavioral, and agentic engagement in imagined lessons that used MR for live streaming from different locations. The role-playing teachers mainly used verbal practices and strategies for fostering closeness, as well as giving feedback and evaluations. However, many strategies previously named or found in the literature were not enacted and symbolic MR boundaries were crossed. Based on our results, we derived affordances and future directions for the further design and development of MR for remote learning.